Human Computer Interaction (HCI) as a key constraint in the e-Government and Digitalization of Afghanistan - Elam, Akmal (Technium Social Sciences Journal, 2023)
The e-Government systems and applications in Afghanistan started very well, however, ended up either half way (Passport System) or were completely closed (NPA System). The architecture and development of the systems were based on standard; however, no survey or research was conducted to address Human Computer Interaction, leading the systems to a rather technical and complex user experience. Common people started getting scared of submitting wrong data, paving the way to middlemen (data entry shops) due to the complexity of UI/UX and lack of data in local languages. Human Computer Interaction for the e-Government of the country was as crucial as the development of the systems itself. Ignoring the fact, HCI became a constraint in the e-Government of Afghanistan and systems developed for the population alternatively started being used by the government officials, serving as data entry clerks for the population. In this study, the lack of HCI and its subjects have been addressed from the cognitive psychology, behavioral sciences, arts and design perspectives in the e-Government systems of Afghanistan. A number of e-Government and Digitalization projects have been presented as case studies, providing practical yet valid arguments to demonstrate to Human Computer Interaction as a key constraint in the e-Government of Afghanistan.